Dynamic Behavior in Transition Zones and Long-Term Railway Track Performance - Paixão, André; Varandas, José Nuno; Fortunato, Eduardo (Frontiers in Built Environment, 2021)
Transition zones between embankments and bridges or tunnels are examples of critical assets of the railway infrastructure. These locations often exhibit higher degradations rates, mostly due to the development of differential settlements, which amplify the dynamic train-track interaction, thus further accelerating the development of settlements and deteriorating track components and vehicles. Despite the technical and scientific interest in predicting the long-term behavior of transition zones, few studies have been able to develop a robust approach that could accurately simulate this complex structural response. To address this topic, this work presents a three-dimensional finite element (3D FEM) approach to simulate the long-term behavior of railway tracks at transition zones. The approach considers both plastic deformation of the ballast layer using a high-cycle strain accumulation model and the non-linearity of the dynamic vehicle-track interaction that results from the evolution of the deformed states of the track itself. The results shed some light into the behavior of transition zones and evidence the complex long-term response of this structures and its interdependency with the transient response of the train-track interaction. Aspects that are critical when assessing the performance of these systems are analyzed in detail, which might be of relevance for researchers and practitioners in the design, construction, and maintenance processes.